Implementation of the Principle of Transparency in Village Financial Management in Accordance with Minister of Home Affairs Regulation Number 20 of 2018 A Constitutional Review (Case Study of Jelegong Village, Rancaekek District, Bandung Regency) - Noval Nuraditya; Chaerul Shaleh; Aji Saptaji (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the implementation of transparency principles in the financial management of Jelegong Village, Rancaekek District, Bandung Regency, and review it from the perspective of Siyasah Dusturiyah. Transparency in village financial management is based on the provisions of Law Number 6 of 2014 concerning Villages, Law Number 14 of 2008 concerning Public Information Disclosure, and Permendagri Number 20 of 2018 concerning Village Financial Management as a normative basis for realizing accountability and public information disclosure at the village level. This study uses an empirical juridical approach with a descriptive qualitative method. The results show that 1) the Jelegong Village government has implemented the principle of transparency through the dissemination of financial information in village deliberation forums and public information boards, but its implementation has not been fully optimal due to limitations in information updates, minimal use of digital media, and low levels of community participation; 2) the implementation of transparency in village financial management from the perspective of Siyasah Dusturiyah has, in principle, reflected the values of trust and maslahah, but has not fully realized justice and information disclosure equally for the entire village community.